Pengaruh Disiplin Kerja dan Kompetensi terhadap Kinerja Karyawan pada PT Pos Indonesia (Persero) Cabang Baturaja - Palupi Indah Sari; Darman Syafei; Nourma Wulanda; M. Agus Kurniawan (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the influence of work discipline and competence on employee performance at PT Pos Indonesia (Persero) Baturaja Branch. This study uses a quantitative approach with a survey method. Data was collected through a questionnaire that was distributed to 30 respondents who were active employees of the company. The data analysis technique used is multiple linear regression to determine the influence of independent variables on dependent variables. The results of the partial analysis showed that work discipline had a significant effect on employee performance, with a t-value of 4.728. Competency was also proven to have a significant effect on employee performance, with a t-value of 7.048 and a significance level of 0.000, which is smaller than α = 0.05. Simultaneously, work discipline and competence together had a significant effect on employee performance with an F score of 109,134. The value of the determination coefficient (R Square) of 0.890 indicates that 89.0% of the variation in employee performance can be explained by work discipline and competence, while the remaining 11.0% are influenced by other variables outside the study, such as motivation, job satisfaction, stress level, compensation system, and job design (Nurfitriani, 2022).